PROGRAM SERAWA (SEHAT JIWA DAN RAGA) : DALAM UPAYA MENINGKATKAN KUALITAS HIDUP LANSIA DI UPTD PANTI SOSIAL TRESNA WERDHA NIRWANA PURI KALIMANTAN TIMUR - CAHYONO, DIDIK; FAUZI, MUHAMMAD SUKRON; SISWANTO, SISWANTO; NAHERIA, NAHERIA; CAHYANINGRUM, GYTA KRISDIANA; HUDA, MUCHAMAD SAMSUL (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
The SERAWA (Healthy, Physical, and Spiritual) program is implemented to improve the quality of life of the elderly at UPTD PSTW Nirwana Puri, a social service institution in East Kalimantan, Indonesia. The program adopts a holistic approach, with a focus on physical health, fitness, and mental well-being. Indonesia's elderly population is increasing rapidly, and this demographic shift poses challenges to the health care and social welfare systems. The SERAWA program aims to overcome this challenge by providing comprehensive support to elderly residents in the institution. The program consists of two main components: Health education and psychological support. Health education focuses on promoting a healthy lifestyle, including balanced nutrition, regular exercise, stress management, and chronic disease prevention. Meanwhile, psychological support is provided through group discussions, sharing sessions, and individual counseling to address emotional well-being and prevent loneliness. The results of the program showed a positive impact on the physical health, emotional well-being, and social connectedness of elderly participants. The success of the SERAWA program demonstrates the effectiveness of a holistic approach in improving the quality of life of the elderly and highlights the potential to replicate similar programs in other social institutions across Indonesia. ABSTRAKProgram SERAWA (Sehat, Raga, dan Jiwa) dilaksanakan untuk meningkatkan kualitas hidup lansia di UPTD PSTW Nirwana Puri, sebuah lembaga layanan sosial di Kalimantan Timur, Indonesia. Program ini mengadopsi pendekatan holistik, dengan fokus pada kesehatan fisik, kebugaran, dan kesejahteraan mental. Populasi lansia di Indonesia meningkat pesat, dan pergeseran demografis ini menimbulkan tantangan bagi sistem perawatan kesehatan dan kesejahteraan sosial. Program SERAWA bertujuan untuk mengatasi tantangan ini dengan memberikan dukungan komprehensif kepada penghuni lansia di lembaga tersebut. Program ini terdiri dari dua komponen utama: pendidikan Kesehatan dan dukungan psikologis. Pendidikan kesehatan berfokus pada mempromosikan gaya hidup sehat, termasuk nutrisi seimbang, olahraga teratur, manajemen stres, dan pencegahan penyakit kronis. Sedangkan dukungan psikologis diberikan melalui diskusi kelompok, sesi berbagi, dan konseling individu untuk mengatasi kesejahteraan emosional dan mencegah kesepian. Hasil program menunjukkan dampak positif pada kesehatan fisik, kesejahteraan emosional, dan keterhubungan sosial peserta lansia. Keberhasilan program SERAWA menunjukkan efektivitas pendekatan holistik dalam meningkatkan kualitas hidup lansia dan menyoroti potensi untuk mereplikasi program serupa di lembaga sosial lain di seluruh Indonesia.